Synthesis and Antimicrobial Activity of Some Metal Complexes Derived from 2-(27´-Hydroxyphenyl)benzoxazole - KUMAR, ANIL; KUMAR, DEVINDER (Asian Journal of Chemistry, 2010)
Synthesis, antibacterial and antifungal activity of metal complexes derived from 2-(2'-hydroxyphenyl)benzoxazole has been described.